PERAN GURU KELAS DALAM MENUMBUHKAN KARAKTER PEDULI LINGKUNGAN MELALUI KEGIATAN ECOBRICK DI SDN KARAWACI 1 - Siti Holisoh; Aam amaliyah; Candra Puspita Rini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the importance of understanding the role of classroom teachers in fostering students' environmental care character through ecobrick activities at SDN Karawaci 1, Tangerang City. The background of this research is that some students were still not accustomed to maintaining environmental cleanliness and disposing of waste in the proper place. Therefore, ecobrick activities were chosen as an effort to develop environmental care character from an early age by utilizing plastic waste into useful products. The purpose of this study was to describe the role of classroom teachers in fostering environmental care character through ecobrick activities among fourth-grade students at SDN Karawaci 1, Tangerang City.This study employed a qualitative approach. Data were collected through observation, interviews, and documentation. The research participants consisted of the fourth-grade classroom teacher and fourth-grade students at SDN Karawaci 1, Tangerang City.The findings showed that the teacher played roles as a facilitator, motivator, role model, and guide in implementing ecobrick activities. As a facilitator, the teacher provided the necessary tools and materials and assisted students throughout the ecobrick-making process. As a motivator, the teacher encouraged students by providing motivation, appreciation, and rewards to increase their participation. As a role model, the teacher demonstrated environmentally responsible behavior in daily school activities. As a guide, the teacher directed students through every stage of the ecobrick activity. Through these activities, students became more concerned about environmental cleanliness, developed the habit of disposing of waste properly, and understood the importance of reducing plastic waste. Based on the findings, it can be concluded that the teacher's role through ecobrick activities effectively fostered environmental care character among students at SDN Karawaci 1, Tangerang City.